Excitation functions for (d, x) reactions on 133Cs up to Ed=40 MeV. (April 2016) - Tárkányi, F.; Ditrói, F.; Takács, S.; Hermanne, A.; Baba, M.; Ignatyuk, A.V.
Abstract: In the frame of a systematic study of excitation functions of deuteron induced reactions the excitation functions of the 133 Cs(d, x) 133m, 133mg, 131mg Ba, 134, 132 Cs and 12 9m Xe nuclear reactions were measured up to 40 MeV deuteron energies by using the stacked foil irradiation technique and γ-ray spectroscopy of activated samples. The results were compared with calculations performed with the theoretical nuclear reaction codes ALICE-IPPE-D, EMPIRE II-D and TALYS calculation listed in the TENDL-2014 library. A moderate agreement was obtained. Based on the integral yields deduced from our measured cross sections, production of 131 Cs via the 133 Cs(d, 4n) 131 Ba→ 131 Cs reaction and 133 Ba via 133 Cs(d, 2n) reactions is discussed in comparison with other charged particle production routes. Highlights: Deuteron induced nuclear reactions on natural cesium up to 40 MeV. Stacked foil irradiation technique. Comparison of results with the ALICE-D, EMPIRE-D and TENDL-2014 calculations. Medical radioisotope production.